Transnational habitus : Mariem Hassan as the transcultural representation of the relationship between Saharaui music and Nubenegra records - Gimenez Amoros, Luis (Rhodes University, Faculty of Humanities, Department of Music and Musicology, 2015)
This thesis expands on primary field research conducted for my MMus degree. Undertaken in the Saharaui refugee camps of southern Algeria (2004-2005) that research - based on ethnographic data and the analysis of Saharaui music, known as Haul Â¹- focussed on the musical system, the social context of musical performance and the music culture in Saharaui refugee camps. This doctoral research examines Saharaui Haul music as practised in Spain and is particularly focussed on its entry, since 1998, into the global market by way of the World Music label, Nubenegra records. The encounter between Saharaui musicians and Nubenegra records has created a new type of Saharaui Haul which is different to that played in the refugee camps. This phenomenon has emerged as a result of western music producers compelling Saharaui musicians to introduce musical changes so that both parties may be considered as musical agents occupying different positions on a continuum of tradition and change. Nubenegra undertook the commodification of Saharaui music and disseminated it from the camps to the rest of the world. A musical and social analysis of the relationship between Nubenegra and Saharaui musicians living in Spain will form the basis of the research in this thesis. In particular, Mariem Hassan is an example of a musician who had her music disseminated through the relationship with Nubenegra and she is promoted as the music ambassador of the Western Sahara. I collaborated with her as a composer and performer on her last album, El Aaiun egdat (Aaiun in fire), in 2012Â² and gained first hand insight into the relationship between Mariem and Nubenegra. This thesis reflects on this relationship and my role in facilitating this encounter.
Keywords: Hassan, Mariem, 1958-; Nubenegra Records; Sahrawi (African people) -- Music -- Cross-cultural studies; Sahrawi (African people) -- Music -- Foreign influences; Transnationalism; Cross-cultural studies -- Spain